A micro view on home equity withdrawal and its determinants. Evidence from Dutch households - André Ebner (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
Home equity is the most important part of a household portfolio, but only recently has it become more accessible through innovations in the mortgage market and financial deregulation. This study looks at the factors driving home equity withdrawal on a household level using Dutch survey data and assesses to which degree different theoretical predictions can be empirically supported. There is little evidence that equity withdrawal is used as a buffer against adverse income shocks, with financial motives and life-cycle effects likely to dominate a household's decision. Finally, the study provides first evidence of the impact of changing supply side conditions on home equity withdrawal.
urn:nbn:de:bvb:19-epub-11309-9
Keywords: D1; D9; E2; E4; G2; 330; home equity withdrawal; Dutch housing market; consumption models; Wohnungsbaufinanzierung; Hypothek; Private Verschuldung; Liquiditätsbeschränkung; Schätzung; Niederlande